Taxonomia integrativa : combinando dados morfológicos e moleculares no estudo de pareiorhaphis hystrix (siluriformes, loricariidae) - Fagundes, Patricia Calegari (2019)
Loricariidae is the largest family of Siluriformes, with species widely distributed on the Neotropical Region. Pareiorhaphis hystrix presents a wide distribution within the genus, occurring in the upper and middle Uruguay River and in the Taquari River, in the Laguna dos Patos, southern Brazil. Morphological variations were detected throughout the distribution of P. hystrix, and this work seeks to test the conspecificy in the various occurrence areas. Specimens from six areas of the Uruguay River basin were used: Chapecó, Pelotas, Ijuí, Passo Fundo, middle Uruguay and Canoas; and three in the Taquari River basin: upper Antas, middle Antas, and Prata. A variance analysis (ANOVA) was performed for the meristic data, and a Principal Component Analysis (PCA) and a Linear Discriminant Analysis (LDA) for morphometric data. The molecular analysis used four mitochondrial genes (coI, cytb, 16S and 12S), analyzing nucleotide diversity, haplotypes, genetic distance, molecular variance (AMOVA), and delimitation of possible species through the “Generalized Mixed Yule Coalescent" (GMYC) method, and the phylogenetic relationships through Bayesian inference. ANOVA presented some significant values (p<0.05) (for example, number of premaxillary teeth, number of dentary teeth), and a significant differentiation was observed between the hydrographic basins, with the exception of the Pelotas River, more closely related to Taquari basin. The PCA indicated a tendency of overlap between areas, while the LDA separated the basins of Taquari River and the Uruguay River, with the exception of the Pelotas which was grouped with the Taquari areas, being the measures with greater discriminatory power the length of the caudal peduncle (LDA1) and anal-fin spine (LDA2). In addition, adult specimens from the Uruguay River basin presented platelets on the abdomen, absent in specimens from the Taquari and Pelotas rivers. The molecular data, with are alignment of 2,518 base pairs (concatenated genes) indicated a nucleotide diversity lower than the haplotypic diversity, suggestive of recent expansion. The concatenated haplotype network points differentiation whitch is between areas, with each locality presenting unique and non-shared haplotypes, although there were few mutational steps in general. AMOVA indicated genetic structuring (differentiation between areas = 50.6%, FST = 0.5 *, cytb), best observed by the pairwise FST distance between areas. The coalescence-based species delimitation analysis (GMYC) was not efficient for interspecific separation for both coI and cytb, although both suggested the presence of OTUS, this separation is not clear. The two areas better genetically defined were the Chapecó and Passo Fundo rivers. In general, the data suggest a subtle morphological variation by hydrographic basin, while the genetic data indicates a weak population structuration by hydrographic areas, but still insufficient for species differentiation between the areas. The joint analysis of morphological and molecular the data allows to conclude that Pareiorhaphis hystrix is composed of a single biological species.